Ebed-Melech’s protest to King Zedekiah as a model of modern protest movement (Jr 38:1–17) - David T. Adamo (In die Skriflig, 2019)
Generally, there are three types of protest, namely prophetic, political and sacramental protests. The prophetic protest has to do with various prophets protesting against nations, kings and policies of the government. Political protests have to do with various groups of people protesting against government policies of oppression. Protest by a group of people of certain faith against the evil that is perpetrated by governments or other authorities is known as sacramental protest. This article is about an individual called Ebed-Melech who protested against the wicked act of King Zedekiah and his princes. The article discusses how Ebed-Melech’s protest, just as the prophetic, political and sacramental protest, can become a model for modern protests all over the world. This article insists that Ebed-Melech’s courage, concern for justice, love, kindness and compassion makes him suitable to be a model for prophetic, political and sacramental protests in the modern world. The Ebed-Melech protest is an example of individual responsibility in the modern world that is filled with injustice.